Dirt and pesticides in horticulture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Willie Makumbe, an agricultural adviser in Zimbabwe, describes typical problems faced by small scale farmers in keeping their produce clean and safe.